Peran Penguasaan Diri dalam Mencapai Kesuksesan: Perspektif Psikologis - Time Halawa; Dorlan Naibaho (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The role of self-mastery in achieving success from a psychological perspective. Self-mastery is a person's ability to control their emotions, behavior and thoughts in facing challenges and achieving goals in life. In the educational context, self-control is very important because it influences students' motivation, discipline and learning abilities. This research highlights the relationship between self-mastery and academic achievement, social skills, and life satisfaction. The results of this research can provide practical guidance for individuals in developing their self-mastery to achieve success in various aspects of